The effect of nitrogen ion implantation on the physical and dielectric properties of cobalt-doped PZT ceramics - Benya Cherdhirunkorn (2020)
© 2019 Cobalt-doped PZT ceramics (Pb(Zr0.52Ti0.48)1-xCoxO3, where x = 0.005, 0.010, 0.015 and 0.02, were implanted by nitrogen ions at 70 keV with fluences of 1 × 1017 and 5 × 1017 ions/cm2. XRD patterns showed that, following nitrogen ion implantation, the perovskite structure was maintained but a higher intensity and more sharp (2 0 0) peak was observed, indicating the occurrence of structural distortion and/or ferroelastic domain switching in the near-surface region. Polarisation-electric field hysteresis loop measurements indicated the reduction of saturation polarization, remanent polarization, and coercive field for all samples implanted at the highest N+-ion fluence of 5 × 1017 ions/cm2. The dielectric properties showed reductions in both relative permittivity and dielectric loss, indicating a hardening effect in these nitrogen-ion-implanted samples.